ZIF-8 Nanoparticles Induce Behavior Abnormality and Brain Oxidative Stress in Adult Zebrafish (Danio rerio) - Liang Jin; Sijing Wang; Chen Chen; Xuchun Qiu; Chong-Chen Wang (MDPI AG, 2023)
Zeolitic imidazolate framework-8 nanoparticles (ZIF-8 NPs) are typical metal-organic framework (MOF) materials and have been intensively studied for their potential application in drug delivery and environmental remediation. However, knowledge of their potential risks to health and the environment is still limited. Therefore, this study exposed female and male zebrafish to ZIF-8 NPs (0, 9.0, and 90 mg L−1) for four days. Subsequently, variations in their behavioral traits and brain oxidative stress levels were investigated. The behavioral assay showed that ZIF-8 NPs at 90 mg/L could significantly decrease the locomotor activity (i.e., hypoactivity) of both genders. After a ball falling stimulation, zebrafish exposed to ZIF-8 NPs (9.0 and 90 mg L−1) exhibited more freezing states (i.e., temporary cessations of movement), and males were more sensitive than females. Regardless of gender, ZIF-8 NPs exposure significantly reduced the SOD, CAT, and GST activities in the brain of zebrafish. Correlation analysis revealed that the brain oxidative stress induced by ZIF-8 NPs exposure might play an important role in their behavioral toxicity to zebrafish. These findings highlight the necessity for further assessment of the potential risks of MOF nanoparticles to aquatic species and the environment.